Analisis Sikap Konsumen Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen Aplikasi Tiket Online Traveloka - Nurlina (CV. Multi Kreasi Media, 2022)
Traveloka is a startup company engaged in Online Travel Agent which was founded in 2012 and conducts the business of selling tickets online. Seeing the huge opportunity for OTAs, there are many new OTAs emerging and increasing competition in Indonesia. This makes Traveloka have to retain its customers while maintaining repurchase interest. This study aims to see the effect of consumer attitudes and service quality on consumer buying interest in the Traveloka online ticket application. This study uses quantitative methods with 108 respondents in Jakarta. The results of the research are stating that the variable of consumer attitudes partially has a positive effect on buying interest. Even though the results of this research are good, it is better for the delivery service application providers to provide member loyalty programs, so that consumers will continue to use this application. Meanwhile, the service quality variable partially has a positive effect on buying interest. Even though the results of this study are good, it is better for the Traveloka online ticket provider application providers to provide after-sales service programs so that consumers increasingly trust the quality of services provided by Traveloka online ticket providers. Together, the variables of consumer attitudes and service quality have a simultaneous effect on buying interest. Even though the results of this study are good, it is better for the delivery service application providers to provide relationship marketing programs, especially warranty services, so that consumers are very happy to use this Traveloka online ticket application.